2010
DOI: 10.1007/s00101-010-1790-y
|View full text |Cite
|
Sign up to set email alerts
|

Notärztliche Einsatzdokumentation in der Simulation

Abstract: Patient safety can be reduced if relevant preclinical data are not transmitted correctly to the admitting hospital. Therefore there is a need to improve documentation quality in EMS. Electronic documentation, training of EMS staff and quality management programs might offer solutions. Because of the small sample size further studies are needed to evaluate the validity of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…26 In a simulation study, Bergrath et al were able to show that, especially in the simulated polytrauma scenario, documentation quality suffered under the dynamic situation. 27 In this study, both groups showed a high number of undocumented criteria; in contrast to Brokmann et al, 22 a better documentation of the collected parameters by the tele-EMS physicians could not be shown. This might be because the CSR-and NEXUS-criteria are not included in the tele-EMS physicians checklist-based documentation system.…”
Section: Choice Of Immobilization Devicecontrasting
confidence: 86%
“…26 In a simulation study, Bergrath et al were able to show that, especially in the simulated polytrauma scenario, documentation quality suffered under the dynamic situation. 27 In this study, both groups showed a high number of undocumented criteria; in contrast to Brokmann et al, 22 a better documentation of the collected parameters by the tele-EMS physicians could not be shown. This might be because the CSR-and NEXUS-criteria are not included in the tele-EMS physicians checklist-based documentation system.…”
Section: Choice Of Immobilization Devicecontrasting
confidence: 86%
“…This particularly affects the collection of medical history and physical examination results [24]. A video-based error analysis, as conducted by Bergrath et al, of documentation by physicians, following simulation, showed that 20% of the information was missing and 22% of the documented information was incorrect [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Incomplete documentation was found in 14% of patient records; although it might not contribute to an HI, it contributes substantially to NM, thus emerging as an important area for improvement in the EMS. One study [ 46 ] simulated the actions of EMS clinicians during medical or traumatic emergency care of a patient. The video-recorded actions were later compared with the documentation, and they revealed missing documentation in 22% of medical cases and 14% of traumatic cases.…”
Section: Discussionmentioning
confidence: 99%